2017
DOI: 10.1002/geo2.45
|View full text |Cite
|
Sign up to set email alerts
|

A new high‐resolution nationwide aboveground carbon map for Brazil

Abstract: Brazil is home to the largest tracts of tropical vegetation in the world, harbouring high levels of biodiversity and carbon. Several biomass maps have been produced for Brazil, using different approaches and methods, and for different purposes. These maps have been used to estimate historic, recent, and future carbon emissions from land use change (LUC). It can be difficult to determine which map to use for what purpose. The implications of using an unsuitable map can be significant, since the maps have large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
(76 reference statements)
0
22
0
1
Order By: Relevance
“…The biomass map accounts for native vegetation aboveground and belowground, live biomass, deadwood, and litter for specific vegetation types across the country. This represents large improvements in relation to the map of the Second National Communication (SCN, acronym in Portuguese) 54 . In summary, these advances are the following:…”
Section: Land Use Modellingmentioning
confidence: 97%
“…The biomass map accounts for native vegetation aboveground and belowground, live biomass, deadwood, and litter for specific vegetation types across the country. This represents large improvements in relation to the map of the Second National Communication (SCN, acronym in Portuguese) 54 . In summary, these advances are the following:…”
Section: Land Use Modellingmentioning
confidence: 97%
“…Based on existing biomass maps and an up-to-date Land Use and Land Cover (LULC) map, Englund et al [104] presented a new high resolution (50 m) nation-wide aboveground carbon map for Brazil. They evaluated this map with an independent reference dataset from Avitabile et al [103], and found high consistency between the two datasets with a corresponding R 2 of 0.59.…”
Section: A New High-resolution Nation-wide Aboveground Carbon Map Formentioning
confidence: 99%
“…Below is a description of the methodology steps: We estimated the carbon dioxide (CO 2 ) emissions for the two future scenarios using the following approach. First, using the function Zonal Statists from ArcGIS 10.3, we calculated for each scenario the total aboveground carbon (AGC) within the cells at risk of deforestation [18]. Next, we converted the AGC to CO 2 , by multiplying by 44/12 (units of CO 2 per units of carbon).…”
Section: Assessing Risk Of Future Deforestation and Co 2 Emissionsmentioning
confidence: 99%